Apresentação PBCIB n.2 v.8, 2013 - Freire, Gustavo Henrique de Araújo; Freire, Isa Maria; Araújo, Vânia Maria Rodrigues Hermes de (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Apresentação PBCIB n.2 v.8, 2013